Tonsea Recycle Center Web-App Development using PXP Method - Aldy Oscar Pancasila Loing; Benny Pinontoan; Mahardika Inra Takaendengan; Christian Alderi Jeffta Soewoeh; Yohanes Andreas Robert Langi; Dodisutarma Lapihu (Jurnal Informatika dan Rekayasa Perangkat Lunak, 2026)
The management of waste banks often encounters issues such as manual transaction processing, limited transparency, and low public participation in waste sorting and recycling. This study presents the development of a web-based application for the Tonsea Recycle Center (TRC) aimed at improving operational efficiency, data transparency, and user engagement through a point-based reward mechanism. The development process adopted the Personal Extreme Programming (PXP) methodology, encompassing stages of requirement analysis, system design, implementation, testing, deployment, and maintenance. The application was developed using HTML, CSS, Python, Django, and SQLite, and includes features such as user authentication, transaction management, a reward point system, and an administrative dashboard[1]. Functional testing, user acceptance testing (UAT), and security testing were conducted to evaluate the system. The results demonstrate that the application effectively overcomes the limitations of the manual system by automating transaction records, enabling real-time data access, and enhancing transparency. Positive user feedback from UAT confirmed the system’s usability and functionality. This research concludes that the TRC web application significantly contributes to improving waste bank operations and community involvement. Future enhancements are suggested, including integration with digital payment systems, AI-based waste classification, and mobile application development to increase system accessibility and utility.